2017
DOI: 10.1007/s00403-017-1755-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum/plasma adiponectin levels and immune-mediated diseases: a meta-analysis

Abstract: Adiponectin plays an important role in the development of immune-mediated diseases. Currently published data regarding the relationship between serum/plasma levels of adiponectin and immune-mediated diseases are inconsistent. We therefore conducted this meta-analysis to explore the association of serum/plasma adiponectin levels with immune-mediated diseases in humans. Systematic literature search was conducted to identify all relevant studies. The study quality was assessed by the Newcastle-Ottawa scale. Poole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…In contrast to metabolic disorders, a high HMW serum level in autoimmune diseases seems to exacerbate chronic inflammation through a pro-inflammatory reaction of HMW. Patients with autoimmune disease show continuous production of HMW, and the severity of their symptoms had a positive relationship with the serum HMW level [122,123]. In addition, both NF-κB and TNF-α are consistently stimulated in patients with autoimmune diseases [137].…”
Section: Issues Related To Hmw: Pro-inflammatory or Anti-inflammatorymentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast to metabolic disorders, a high HMW serum level in autoimmune diseases seems to exacerbate chronic inflammation through a pro-inflammatory reaction of HMW. Patients with autoimmune disease show continuous production of HMW, and the severity of their symptoms had a positive relationship with the serum HMW level [122,123]. In addition, both NF-κB and TNF-α are consistently stimulated in patients with autoimmune diseases [137].…”
Section: Issues Related To Hmw: Pro-inflammatory or Anti-inflammatorymentioning
confidence: 98%
“…Adiponectin is increased in some diseases with chronic inflammation such as RA, CKD, IBD, type 1 diabetes, cystic fibrosis, and systemic lupus erythematosus (SLE) [76]. In addition, other studies showed that patients with systemic autoimmune diseases have elevated adiponectin serum levels [122,123]. However, the reasons why adiponectin is positively associated with autoimmune diseases have not been elucidated, and adiponectin's role in inflammation remains controversial.…”
Section: Pro-inflammatory Role Of Adiponectin In Inflammatory Bowel Dmentioning
confidence: 99%
“…A large number of observational epidemiological studies have been undertaken to investigate the role of adipokines in the occurrence and progression of RA. Two recent meta-analyses of case-control studies demonstrated that circulating adiponectin levels could be signi cantly higher in the RA patients than those in the health controls [30,31]. However, it was also reported separately that adiponectin levels were not related to RA activity [30,32].…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin can inhibit the phagocytic activity of macrophages, reduce the production of tumor necrosis factor alpha and gamma interferon, as well as induce the production of interleukin 10 and interleukin 1 receptor antagonists which are antiinflammatory molecules. However, serum/plasma levels of adiponectin are higher in immune-mediated diseases [17,18]. In contrast, in obese patients, adiponectin levels are lower than controls, and it has been observed that production of this adipocytokine increases after weight loss [19].…”
Section: Leptin and Adiponectinmentioning
confidence: 99%